2017
DOI: 10.1002/cphc.201601244
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Quantum Many‐Body Perturbation on Spin and Charge Separation in the Excited States of the Synthesized Donor–Acceptor Hybrid PBI–Macrocycle Complex

Abstract: The reliable calculation of the excited states of charge-transfer (CT) compounds poses a major challenge to the ab initio community because the frequently employed method, time-dependent density functional theory (TD-DFT), massively relies on the underlying density functional, resulting in heavily Hartree-Fock (HF) exchange-dependent excited-state energies. By applying the highly sophisticated many-body perturbation approach, we address the encountered unreliabilities and inconsistencies of not optimally tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…[47][48][49][50][51] The range separation parameter can be empirically optimized 47,52,53 or tuned from first principles, by choosing ω such that the eigenvalue of the Kohn-Sham frontier orbital located in the solute approaches the ionization energy. 54,55 The optimally tuned (OT) RSH functionals have been used with great success for the prediction of chargetransfer excitations for a variety of complex molecular systems, [56][57][58] intermolecular interactions, 59 and dielectric screening. 55,59 In fact, the introduction of the non-local EXX term at long range in the RSH seems to be appropriate for introducing the correct fieldcounteracting behavior due to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51] The range separation parameter can be empirically optimized 47,52,53 or tuned from first principles, by choosing ω such that the eigenvalue of the Kohn-Sham frontier orbital located in the solute approaches the ionization energy. 54,55 The optimally tuned (OT) RSH functionals have been used with great success for the prediction of chargetransfer excitations for a variety of complex molecular systems, [56][57][58] intermolecular interactions, 59 and dielectric screening. 55,59 In fact, the introduction of the non-local EXX term at long range in the RSH seems to be appropriate for introducing the correct fieldcounteracting behavior due to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] In recent years, the OT-RSH approach has been used successfully to predict a wide range of charge-transfer phenomena (see, e.g., Refs. [18][19][20][21][34][35][36][37]. However, to the best of our knowledge it has rarely been used for the calculation of electronic coupling 38 and its accuracy has not been systematically assessed.…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, the number of publications using the BSE/ GW approach to model molecular (i.e., finite) systems has been relatively reduced until 2010, but it has been exploding since then. , In a recent contribution, we found that the accuracy provided by BSE/ev GW was as high (actually even slightly superior for the tested set) as the one reached with the CASPT2 approach for (vertical) ES energies, whereas in a previous work devoted to 0–0 energies of large chromogens, we found that BSE/ev GW , ADC(2), and CC2 similarly reproduced experimental data with average errors of ca. 0.15 eV, that is, smaller than the one obtained with TD-DFT for the same data set .…”
Section: Introductionmentioning
confidence: 77%